Innovation in a Capstone Course in Youth Work: Using the Authentic Situated Learning and Teaching Framework - Hovington, Stéphanie; Blanchet-Cohen, Natasha; Mann-Feder, Varda (International Journal of Child, Youth and Family Studies, 2020)
Capstone courses often focus on applied learning, typically practicum experiences such as internships. However, students do not always benefit as much as they could from their internships because teaching and learning resources are not used optimally. This paper explores the use of project-based learning in a capstone course of the Graduate Diploma in Youth Work program at Concordia University that includes an in-class seminar and an internship in a human services agency. Using the principles of context authenticity and cognitive apprenticeship from the Authentic Situated Learning and Teaching (ASLT) framework, we examine the experiences of two cohorts of interns (24 students in all). An analysis of their final papers and participation in a focus group, as well as the results of the university’s course evaluation, suggests that the ASLT framework contributes to the transfer of learning in a professional setting. Furthermore, the use of the psychoeducative model to structure active pedagogies in a youth work capstone course provides a means for planning therapeutic activities and organizing intervention programs that help develop competencies to work in diverse settings.